Potential Antimicrobe Producer of Endophytic Bacteria from Yellow Root Plant (Arcangelisia flava (L.)) Originated from Enggano Island - null Sipriyadi; null Masrukhin; Risky Hadi Wibowo; Welly Darwis; Salprima Yudha; Ismu Purnaningsih; Resli Siboro (International Journal of Microbiology, 2022)
Exploration studies of endophytic bacteria from Arcangelisia flava (L.) and their potential have not much been conducted. This research aims to explore and characterize the antimicrobial activity of endophytic bacteria in A. flava against pathogenic bacteria. This research consists of several steps including the isolation of bacteria, screening of the antimicrobial activity assay using the dual cross streak method, molecular identification through 16s rDNA analysis, and characterization of bioactive compound production through PKS-NRPS gene detection and GC-MS analysis. There are 29 endophytic bacteria that were successfully isolated from A. flava. The antimicrobial activity showed that there are four potential isolates AKEBG21, AKEBG23, AKEBG25, and AKEBG28 that can inhibit the growth of pathogenic bacteria such as Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. The 16S rDNA sequence analysis showed that these isolates are identified as Bacillus cereus. These four isolates are identified as able to produce the bioactive compounds through the detection of polyketide synthase (PKS) and nonribosomal peptide synthase (NRPS)-encoding genes. B. cereus AKEBG23 has the highest inhibition against pathogenic bacteria, and according to the GC-MS analysis, five major compounds are allegedly involved in its antimicrobial activity such as butylated hydroxytoluene (BHT), diisooctyl phthalate, E-15-heptadecenal, 1-heneicosanol, and E-14-hexadecenal. This result suggested that B. cereus AKEBG23 as the endophytic bacterium from A. flava has a beneficial role as well as the plant itself. The bacterium produces several bioactive compounds that are allegedly involved in its antimicrobial activity against pathogenic bacteria.